Leadership regeneration and sustainable governance in community-based tourism villages: A comparative institutional analysis - Ainul Luthfiana (Ecotourism and Environment Conservation, 2026)
Background: Leadership sustainability has become a critical challenge for community-based tourism villages, particularly in governance systems that rely on informal succession and community legitimacy. While prior studies emphasize capacity building and participation, empirical attention to leadership regeneration as an institutional governance process remains limited. This study addresses this gap by examining leadership regeneration across different tourism village governance contexts. Methods: This study adopts a qualitative, theory-driven design integrating organizational theory, human capital theory, and talent management theory. Thematic coding and systematic comparative analysis were applied to secondary qualitative data from three tourism villages in Yogyakarta (Nglanggeran, Wukirsari, and Pentingsari) using multi-stage coding, interpretive synthesis, and cross-case pattern matching. Findings: The results indicate that leadership regeneration remains predominantly informal and experience-based, relying on mentoring networks, role rotation, and social legitimacy rather than structured succession systems. Villages with semi-formal governance structures exhibit stronger leadership learning routines, whereas community-centered models prioritize social cohesion over institutional continuity. Key barriers include limited administrative capacity, cultural governance norms, and weak leadership pipeline mechanisms. Youth participation emerges as a critical leverage point, particularly through digital governance innovation and creative tourism initiatives. Conclusion: Leadership regeneration should be conceptualized as a cyclical institutional process integrating governance structure, human capital circulation, leadership talent pathways, and stakeholder collaboration ecosystems. The proposed framework offers practical guidance for strengthening leadership sustainability in community-based tourism governance. These findings strengthen the understanding of leadership regeneration within community-based tourism governance and contribute to sustainable tourism governance practices in rural destinations. Novelty/Originality of this Article: This study contributes by integrating cross-theoretical perspectives with comparative empirical evidence to reconceptualize leadership regeneration as a dynamic governance system rather than a linear succession event, offering an empirically grounded and policy-relevant analytical model.